Microplastic abundance at differences agricultural practices: a case study in Tanjong Karang, Selangor - Saharudin, Nurul Shafiqah (2023)
Microplastic contamination has become a huge concern in the wide range of ecological, with agricultural activities being a significant source of microplastics in soils. Numerous plastic items are employed in the process of agricultural production which leads to the generation of a huge number of microplastics. Therefore, the microplastic contamination in agricultural areas required being investigated urgently. In this study, we determined the occurrence of microplastic in soil and water at difference agricultural practices of Tanjong Karang, Selangor. This study proclaims the occurrence and characteristics of microplastic pollution in typical farmland soils and irrigation water of suburb land using Stereomicroscopes and μ- FTIR for identification and verification of microplastic. Microplastics pollution characteristics (shape, size, colour) was revealed in mulch and non-mulching farmlands soil and in their irrigation water. Non-mulched soils contained much higher abundances of microplastics than mulched soils. Non-mulching soils contained larger amounts of microplastics than nonmulching soils, with 130 pieces kg−1 and 121.25 pieces kg−1, respectively, on average. Microplastics were mainly fragments, films, foam and fibre, and mulched soils had much higher percentage of films, than non-mulched soils that had greater proportion of fragment. Furthermore, the use of nearby water sources increases the abundance of microplastic in the soil, with fibre being the most abundant in the water, where there was enough evidence to conclude that there is a significant linear relationship between fibre microplastic type in soil and irrigation in both areas. Mulched soils had much lower proportion of microplastics <0.5 mm than non-mulched soils and white microplastics account for the highest proportion in both fields. Multiple polymers, e.g., Polyethylene terephthalate (PET), polyester, polypropylene (PP), polyvinyl chloride (PVC), polyethylene (PE), and polyamide were found in the soil microplastics indicate contributions from irrigation and plastic waste residues from farming practices. PET, PE, and PVC were the dominated polymer compositions. Overall, this study may serve as a valuable basis for further investigation into the circumstances behind the presence of microplastics in agricultural areas. In the future, more focus should be placed on associated remediation and management techniques to lessen microplastics-based mulching contamination and the establishment of effective recycling technologies to combat agricultural waste.